2016
DOI: 10.1063/1.4958732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mo insertion layers on the magnetoresistance and perpendicular magnetic anisotropy in Ta/CoFeB/MgO junctions

Abstract: The effect of a thin Mo dusting layer inserted at the interface of Ta/CoFeB of perpendicular magnetic tunneling junction with MgO barriers was investigated. Unlike thick Mo layers that exhibited a strong (110) crystalline texture, the inserted Mo layer between Ta/CoFeB had little negative influence on the crystallization of CoFe (001), therefore combining the advantages of Mo as a good thermal barrier and Ta as a good boron sink. For optimized Mo dusting thickness, a large tunneling magnetoresistance of 208% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…These features are mainly attributed to the B affinity of W and the strong PMA generated at the W/CoFeB interface. Similar results have been reported in several literatures . These findings benefit the compatibility of p‐MTJs with standard CMOS back‐end‐of‐line processes and make W and Mo more attractive than Ta for practical applications.…”
Section: Modulation Of Hm/fm Interface For Strong Pmasupporting
confidence: 89%
See 2 more Smart Citations
“…These features are mainly attributed to the B affinity of W and the strong PMA generated at the W/CoFeB interface. Similar results have been reported in several literatures . These findings benefit the compatibility of p‐MTJs with standard CMOS back‐end‐of‐line processes and make W and Mo more attractive than Ta for practical applications.…”
Section: Modulation Of Hm/fm Interface For Strong Pmasupporting
confidence: 89%
“…Consequently, by replacing the typical Ta layer with the Mo layer, a thermally robust perpendicularly magnetized CoFeB/MgO system could be realized. This result also suggested that there was little Mo diffusion during the high temperature annealing due to the large formation energy of Mo–Fe alloys . Besides, after annealing, interfaces in Mo (5 nm)/CoFeB (1.2 nm)/MgO (2 nm)/CoFeB (1.2 nm)/Mo (5 nm) stack are very neat, which is shown by the high‐resolution transmission electron microscopy (HR‐TEM) image in Figure a.…”
Section: Modulation Of Hm/fm Interface For High Tmrmentioning
confidence: 85%
See 1 more Smart Citation
“…To increase the free(storage)-layer volume, V, and thus to improve the data retention, while keeping a strong PMA, two FeCoB/MgO interfaces may be used 1 . To absorb the boron out of the FeCoB layers upon the post-deposition anneals required to recrystallize the MgO barrier and the FeCoB ferromagnetic (FM) electrodes, a thin metal (e.g., Ta, W) spacer is usually introduced in the middle of the FeCoB storage layer [2][3][4][5][6][7] . Besides improving the data retention, the double-MgO storage layer also exhibits a reduced Gilbert damping, α, as compared to thinner ones sandwiched between a single MgO barrier and a heavymetal layer such as Ta or W. In the latter structures, a damping enhancement is often observed resulting from the spin-pumping effect.…”
Section: Introductionmentioning
confidence: 99%
“…with large TMR, careful control of the oxidation level results in the high Keff value that we observe here [33] [32]. If the bottom layer were considered as an isolated particle, its thermal stability factor = 47±2 and the anisotropy field is =>>, @ABBAC = 14.3 ± 1.3 kOe.…”
Section: Resultsmentioning
confidence: 66%